2004
DOI: 10.1007/s00125-003-1319-x
|View full text |Cite|
|
Sign up to set email alerts
|

Common genetic polymorphisms in the promoter of resistin gene are major determinants of plasma resistin concentrations in humans

Abstract: Aims/hypothesis. Resistin is thought to be an important link between obesity and insulin resistance. It has been suggested that genetic polymorphism in the promoter of resistin gene is a determinant of resistin mRNA expression and possibly associated with obesity and insulin resistance. In this study, we investigated the association between the genotype of resistin promoter and its plasma concentrations. Methods. We examined g.-537A>C and g.-420C>G polymorphisms in the resistin promoter and measured plasma res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
147
2
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 157 publications
(173 citation statements)
references
References 28 publications
(48 reference statements)
15
147
2
2
Order By: Relevance
“…We also reported that this polymorphism was important in determining plasma resistin levels [21]. In that study, plasma resistin levels of the −420G/G genotype group were higher than those of the −420C/C genotype group.…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations
“…We also reported that this polymorphism was important in determining plasma resistin levels [21]. In that study, plasma resistin levels of the −420G/G genotype group were higher than those of the −420C/C genotype group.…”
Section: Introductionmentioning
confidence: 71%
“…Several polymorphisms have been found in the promoter region of the resistin gene and it has been reported that one polymorphism, −420 C>G, was related to plasma resistin levels and diabetes [20,21,30]. In this study, we investigated the molecular mechanism underlying the effect of the −420G/C variation on the expression of the resistin gene.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…For example, although many studies report a lack of association between resistin gene variants and type 2 diabetes [4][5][6]10,[20][21][22][23][24][25], only one of these analyzed a sample population larger than 1000 subjects [4]. When data from three of the negative result studies [20][21][22] were analyzed together with new samples in a meta-analysis of 3536 subjects, the combined results showed an association between the −420C>G variant (RETN5) and diabetes [26].…”
Section: Discussionmentioning
confidence: 99%